"What the F---": Taboo Words in the TV Series Sex Education - Brilliannisa Syahri Syahidna; Ni Gusti Ayu Roselani (Lexicon, 2023)
This study investigates the functions of taboo words used by male, female, young and adult characters in the first season of Sex Education. Azzaro (2005) and Allan & Burridge's (2009) functions of taboo words were furthermore employed to identify and classify the use of taboo words in the TV series. There were 114 utterances of taboo words in the TV series. The most common function is swearing or expletive expression (53.51%), followed by insults or abusive expression (29.82%), and the least used functions are expression of social solidarity (11.40%) and stylistic choice (5.26 %). In regards to gender, both male and female use taboo words at nearly the same frequency. In fact, 58 out of 114 taboo words and expressions were used by female characters and 56 by male characters. Moreover, with respect to age group, young characters or teenagers in Sex Education appear to use taboo words more frequently than the adult characters. Overall, 83 out of 114 taboo words and expressions were used by teenage characters and 31 by adult characters. In addition, there are frequency differences in the use of taboo words in four specific gender and age groups. Those groups are young male, adult male, young female, and adult female.Keywords: taboo words, functions, gender, age, and TV series